The Urgency of Employment Law for Informal Sector Workers in the Welfare State Concept - Rinto Angga Puja Kesuma; Tahta Radya Panigarahardja; Fahma Pantria; Angga Putra Adi Pratama; Jan Alizea Sybelle (Proceeding International Conference Restructuring and Transforming Law, 2023)
The aim of this research is to re-evaluate the importance of labor laws for informal sector workers within the framework of the Indonesian welfare state concept. The research technique involves studying a normative legal approach or documents or literature that only focuses on labor law currently in force in Indonesia. Qualitative methods of technical analysis are used to explain relationships between objectively determined phenomena, concepts, data, or facts. Based on the results of this research, the Employment Law in Indonesia still ignores the rights, dignity, standard of living, and even the work environment of workers in the informal sector. The National Employment Law has legal loopholes because it does not provide legal protection, guarantees and social security for informal sector workers. This demand is contrary to the concept of Pancasila and the 1945 Republic of Indonesia Constitution. Therefore, the government is expected to work together with the legislature to improve the Labor Law so that all parties are in the same position in the production process so that companies can develop. Meanwhile, these efforts are generally expected to lead to harmonization of laws for informal sector workers in the field of employment, especially in the Indonesian welfare state.